2000
DOI: 10.1161/01.res.87.12.1195
|View full text |Cite
|
Sign up to set email alerts
|

Role of NAD(P)H Oxidase in Angiotensin II–Induced JAK/STAT Signaling and Cytokine Induction

Abstract: Abstract-Inflammatory processes involve both synthesis of inflammatory cytokines, such as interleukin-6 (IL-6), and the activation of their distinct signaling pathways, eg, the janus kinases (JAKs) and signal transducers and activators of transcription (STAT). Superoxide (O 2 Ϫ ) anions activate this signaling cascade, and the vasoconstrictor angiotensin II (Ang II) enhances the formation of O 2 Ϫ anions via the NAD(P)H oxidase system in rat aortic smooth muscle cells. Ang II activates the JAK/STAT cascade via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
185
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(198 citation statements)
references
References 39 publications
7
185
1
5
Order By: Relevance
“…Antioxidants Inhibit Thrombin-stimulated JAK2 Phosphorylation-Reactive oxygen species (ROS)-dependent activation of JAK2 has been reported in rat VSMC treated with Ang II (45). Because thrombin also generates ROS in VSMC (58), we investigated whether antioxidants inhibit thrombin-induced activation of JAK2.…”
Section: Figmentioning
confidence: 99%
“…Antioxidants Inhibit Thrombin-stimulated JAK2 Phosphorylation-Reactive oxygen species (ROS)-dependent activation of JAK2 has been reported in rat VSMC treated with Ang II (45). Because thrombin also generates ROS in VSMC (58), we investigated whether antioxidants inhibit thrombin-induced activation of JAK2.…”
Section: Figmentioning
confidence: 99%
“…Recent findings have suggested that Ang II activates intracellular signaling processes, including the polyol pathway and generation of reactive oxygen species (ROS) (8,9). In cell systems, a major source of Q. Pan et al…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (5) suggest that a significant source of intracellular ROS in cardiovascular cells is a phagocyte-type NADPH oxidase. AngII activates NADPH oxidases in vascular smooth muscle (5,6), fibroblasts (7), endothelial cells (EC) (8,9), and cardiomyocytes (10). Furthermore, NADPH oxidase activation and increased ROS production are implicated in AngII-stimulated vascular smooth muscle hypertrophy (3,5) and in AngII-dependent hypertension and the associated endothelial dysfunction (11)(12)(13).…”
mentioning
confidence: 99%